Resection of cervical extra-intraspinal neuromas through the enlarged intervertebral foramen: Results in 34 case series patients - Chang, Chuan; Che, Xiao-Ming; Zhang, Ming-Guang (Frontiers in Surgery, 2023)
Objective The purpose of this study was to analyze the techniques used to resection cervical extra-intraspinal neuromas (also known as cervical dumbbell neuromas) through the enlarged intervertebral foramen. Methods A total of 34 consecutive patients (19 male, 15 female) with cervical dumbbell neuromas reviewed retrospectively between April 2008 and May 2020. Sixteen tumors were found in the intervertebral foramen of C1-C3, four in C3-C4, and 14 in C4-T1. The approach in all cases was to expose the tumors by intermuscular dissection and to remove them through the enlarged intervertebral foramen without excision of any bony structures. However, to expose tumors at different locations, the incisions shall be made accordingly. In this case series, the incisions were made along the posterior border of the sternocleidomastoid muscle for the C1-C3 tumors and along the anterior border of the muscle for the C3-C4 tumors. Transverse incisions were required for the C4-T1 tumors. Results Following the mentioned incising approach, all 34 tumors were completely exposed. 31 were completely removed in one stage, and 3 tumors underwent subtotal resection because of brachial plexus nerve adhesion. The vertebral artery and spinal cord were undamaged for all cases. The patients who had total tumor resection showed no sign of recurrence on enhanced magnetic resonance imaging during follow-ups. The status of patients who underwent subtotal resection was stable after radiation therapy. None of the patients developed spinal instability. Conclusions Cervical dumbbell neuromas can be exposed and removed through the enlarged intervertebral foramen without causing spinal instability or injury to the spinal cord or vertebral artery. This operative approach can retain the integrity of the structures of spine and should be considered the ideal approach for cervical dumbbell neuromas.